Betrayal of Closest Friend in Jay Asher’s Novel “Thirteen Reasons Why” - Loebis, Iin Almeina (International Journal Labs, 2023)
Background: One of the negative actions in human relationships is betrayal. is not a new problem in human relationships. In this era, the phenomenon of betrayal often occurs around us. Betrayal can also occur in all types of human relationships i.e. marriage or romantic relationships, friendships, the world of work, etc. Aim: This study discusses betrayal in the novel Thirteen Reasons Why by Jay Asher. This study aims to reveal the types of friends' betrayal and to describe the impacts of protagonist's friends. Method: The researcher uses Larson's theory (2021) which took about the types of betrayal and Reis and Spencer's theory (2009) about the impacts of betrayal. This study uses a descriptive qualitative method to reveling the data. The data is originally taken from the Thirteen Reasons Why novel. Findings: In this research found five data to reveal the type of betrayal and twelve data to describe the impacts of betrayal. The results of this study indicate that there are two types of betrayal received by Hannah, i.e., intimate partner betrayal and interpersonal betrayal. The researcher also found that the impact that Hannah as a betrayal of her friends received is a loss of trust, a loss of relationship/friendship, and a loss of self-esteem.